Proses Pembuktian Tindak Pidana Pencabulan Terhadap Anak Kandung yang Dilakukan oleh Ayahnya (Lex Jurnalica, 2011)
The problem of abuse within the family environment is not a secret anymore, it is proven by the reports in the media which includes cases of abuse like this is difficult to uncover because it is still considered taboo to be disseminated, and if to tell the other person means it will bring shame on family. Based on the above, then the problem will be the writer suggested the writing of this research is, What about efforts to control the problem of abuse within the family of the child of his father had done? The purpose of this study was to determine the response problems in the family sexual abuse against the child of his father had done. In this paper the authors obtain the necessary data through library research. The nature of this writing is descriptive of a method that takes data in writing to be elaborated so as to obtain a thorough overview and understandingKeywords: Proof, Sexual Abuse, Children